2013
DOI: 10.1152/jn.00375.2012
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-binding protein parvalbumin modulates the firing 1 properties of the reticular thalamic nucleus bursting neurons

Abstract: Albéri L, Lintas A, Kretz R, Schwaller B, Villa AE. The calcium-binding protein parvalbumin modulates the firing 1 properties of the reticular thalamic nucleus bursting neurons. J Neurophysiol 109: 2827-2841, 2013. First published March 13, 2013 doi:10.1152/jn.00375.2012.-The reticular thalamic nucleus (RTN) of the mouse is characterized by an overwhelming majority of GABAergic neurons receiving afferences from both the thalamus and the cerebral cortex and sending projections mainly on thalamocortical neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 104 publications
2
29
0
Order By: Relevance
“…These changes in PV+ cell firing rate could be caused by changes in metabolic genes regulated by PGC-1α (Finck and Kelly 2006); there is abundant evidence for a high metabolic requirement for cortical PV+ interneurons (reviewed in (Jiang, Cowell et al 2013)). A loss of PV itself could contribute to the decreased firing rate, as loss of the calcium buffer in PV knockout mice has been shown to alter intrinsic excitability of GABAergic neurons in the reticular thalamic nucleus (Alberi, Lintas et al 2013). However it is also possible that other factors contribute to this reduction.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in PV+ cell firing rate could be caused by changes in metabolic genes regulated by PGC-1α (Finck and Kelly 2006); there is abundant evidence for a high metabolic requirement for cortical PV+ interneurons (reviewed in (Jiang, Cowell et al 2013)). A loss of PV itself could contribute to the decreased firing rate, as loss of the calcium buffer in PV knockout mice has been shown to alter intrinsic excitability of GABAergic neurons in the reticular thalamic nucleus (Alberi, Lintas et al 2013). However it is also possible that other factors contribute to this reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have shown that for PPI of ASR, several pathways are implicated including direct glutamatergic projections from the cochlear nuclei, inhibitory cholinergic projections from the pedunculopontine tegmental nucleus and indirect inputs from the superior and inferior colliculi [15]. Electrophysiological recordings of cortical, hippocampal and cerebellar neuronal activity in PV−/− mice in vitro showed that the absence of PV in a subpopulation of GABA-ergic interneurons resulted in modification of the dynamics of inhibitory control (for reviews, see [22]), enhancement of the severity of pharmacologically-induced seizures [25], alterations of Purkinje cell-firing [26], and modulation of the firing properties of the reticular thalamic nucleus bursting neurons [1]. Fast-spiking PV-positive inhibitory cells, which represent the largest inhibitory subpopulation in the auditory cortex of the cat, are involved in the sharpening of frequency and intensity tuning and the shaping of spectral modulation preferences [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Parvalbumin is a Ca 2+ buffer protein characterized by a slow-onset Ca 2+ binding that generally does not affect the initial amplitude of Ca 2+ transients, but then accelerates the early phase of the intracellular Ca 2+ concentration, thus affecting short-term plasticity and controlling the intracellular Ca 2+ available to SK channels [30]. Loss of PV leads to enhanced susceptibility to epileptic seizure [12] and modifications of the firing patterns at the thalamocortical level [13,15]. The question is raised whether firing patterns other than the regular firing correspond to distinct cell populations, maybe lying in the border of the nucleus, or whether they are generated by cells that are in a different functional state.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth reporting that lesions of PAG affect states of consciousness [36] and that PAG receives afferences from the prefrontal cortex [37] and projects to intralaminar and midline thalamic nuclei [38]. Moreover, PV is highly expressed in the thalamic reticular nucleus [13] which plays a key role in 'gating' consciousness [39]. These observations taken together with the present findings may suggest that the activity of PV1-nucleus regulates psychomotor functions in the framework of an extended reticular thalamic activating system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation